Enhancing EFL Reading Comprehension through Scramble Word Activities: A Qualitative Study in an Indonesian Vocational High School - Arri Kurniawan; Bagas Ibra Mahendra Sakti; Erlik Widiyani Styati (English Teaching Journal : A Journal of English Literature, Language and Education, 2026)
Reading comprehension is an essential component of English language learning because it enables learners to construct meaning from written texts and supports overall language development. However, many Indonesian vocational high school students continue to experience difficulties in comprehending English texts due to limited vocabulary, low learning motivation, and teacher-centered instructional practices. This study explored the implementation of Scramble Word Activities in teaching reading comprehension to tenth-grade students at SMKN 5 Madiun. Employing a qualitative research design, data were collected through classroom observations, semi-structured interviews with the English teacher, and document analysis. The collected data were analyzed using the interactive model of data condensation, data display, and conclusion drawing, while methodological triangulation ensured the trustworthiness of the findings. The findings revealed that Scramble Word Activities were implemented through pre-reading, while-reading, and post-reading stages that actively engaged students in reconstructing meaningful sentences from scrambled lexical items. The technique promoted vocabulary recognition, sentence organization, collaborative learning, and active participation throughout the reading process. Students demonstrated higher motivation and greater classroom engagement than during conventional reading lessons. Nevertheless, limited vocabulary knowledge and classroom time constraints remained major challenges during implementation. The study concludes that Scramble Word Activities represent an effective interactive strategy for improving reading comprehension in vocational EFL classrooms by fostering meaningful learning and student engagement.